Socio-demographic factors and their impact on quality of life among cancer patients- a study in a tertiary health institute in Jharkhand - K., Jeseena; Rajnish, Sahil Nayan; Bharti, Nivedita; Kumari, Neelanjali (International Journal of Research in Medical Sciences, 2025)
Background: Quality of life (QOL) is a crucial outcome measure in cancer care, reflecting the physical, psychological, and social well-being of patients. Socio-demographic factors such as age, gender, marital status, education, and socio-economic status can significantly influence QOL in cancer patients. Identifying these determinants is essential for developing targeted interventions to improve patient care. Methods: A cross-sectional study was conducted in the oncology department of Rajendra Institute of Medical Sciences (RIMS), including 264 cancer patients aged 18 years and above. Data were collected through structured interviews using a validated QOL questionnaire based on EORTC guidelines, adapted for the Indian population. Socio-demographic data and QOL scores were analyzed using the chi-square test, with statistical significance set at p<0.05. Results: Among the socio-demographic factors assessed, marital status was significantly associated with QOL (p=0.04), with widowed patients reporting the lowest QOL scores. Gender differences, though not statistically significant, indicated that female patients experienced greater psychological distress. Socio-economic status, education level, age, ethnicity, and religion did not show significant associations with QOL. Conclusions: The findings emphasize the importance of marital status as a key determinant of QOL among cancer patients, underscoring the need for psychological and social support interventions. While other socio-demographic factors did not show statistical significance, trends indicate the necessity for patient education and financial support mechanisms to mitigate barriers to effective cancer care.